Analisis Potensi Wisata Bahari Berbasis Sistem Informasi Geografis di Pantai Langala Provinsi Gorontalo - La Ode Juni Akbar; Daud Yusuf; Muhammad Kasim (Jambura Geoscience Review, 2019)
The research aimed to investigate the maritime tourism potential of Langala Beach. The research was conducted in Dulupi Sub-District, Boalemo Regency, Gorontalo Province. The geographical location of the research area is 000 30 04 "LU 1220 29' 11" BT. Data is collected from primary sources and secondary sources. The research uses the triangulation data collection technique, which combines various techniques and data sources. The methods used in this study are survey methods, conformity analysis, in-depth interviews, and regional mapping. The data analysis technique focuses on the percentage assessment of tourism suitability using a marine tourism suitability index analysis for snorkeling and diving, a tourist suitability index analysis for swimming and canoeing, data analysis using the percentage of coral cover per lifeform category for the status of coral reefs. The results of the Langala Beach tourism research for marine tourism (snorkeling and diving) category included in the appropriate category (S2) with a percentage of 80.45% suitability, Langala Beach area for marine tourism category (swimming and canoeing) included in the very appropriate category (S1) with a percentage of suitability level of 93.57%. The condition of coral reefs in the research location, namely station 1, is in the good category with a value of 37.12%, Station 2 and 3 in the medium category with a value of 52.32% and 36.34%.